Gross myofascial release on pain and function in cervical radiculopathy: a randomised controlled study - El-Din Mahmoud, Lama Saad; Mahmoud Aly, Sobhy; Metwally, Hosam Magdy (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Cervical radiculopathy (CR) is frequently associated with myofascial trigger points. Myofascial release (MFR) restores tissue extensibility and reduces symptoms. The purpose of this study was to investigate the effect of gross MFR on pain and function in patients with CR.Methods. Forty patients with CR were allocated to two equal groups; the study group: which received gross MFR combined with a selected, designed program, and the control group: which received the selected, designed program. The patients were assessed using the neck disability index (NDI), Quick Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, cervical range of motion (CROM) measured by goniometer, and Visual Analogue Scale for Pain (VAS-P).Results. The study group showed a significant decrease in the NDI (p = 0.001), quick DASH (p = 0.001), and VAS (p = 0.001) post-treatment compared with that of the control group. Also, there was a significant increase in CROM of the study group compared with that of the control group post-treatment (p = 0.001).Conclusions. Gross MFR using a gross stretch of the posterior cervical musculature and upper quarter (arm pull technique) had significantly improved outcomes in the rehabilitation of CR patients.
Keywords: cervical spondylosis; myofascial release; radiculopathy; cervical spine; cervical pain